0073 A Mexican Spanish Version of the Sleep Disorders Symptom Checklist. (25th May 2022) - Begay, Tommy; Valencia, Dora; Granados, Karla; Delgadillo, Marcos; Ghani, Sadia; Molina, Patricia; Alfonso-Miller, Pamela; Perlis, Michael; Klingman, Karen; Wills, Chloe; Grandner, Michael
Abstract: Introduction: The Sleep Disorders Symptom Checklist (SDSCL-25) is a brief assessment of patient-reported symptoms that suggest risk for a wide range of sleep disorders. To ensure the validity of study subject responses, the SDSCL-25 was translated into Spanish by a bilingual research study team. It was then administered to study subjects in their preferred language. Methods: Data were collected from a sample of N=100 individuals of Mexican Descent in Nogales, Arizona, US-Mexico border. The SDSCL-25 is a screening tool that assesses the presence of a wide range of symptoms for sleep disorders. To translate the measure into Spanish, the following procedure was followed: (1) a bilingual study team member performed an initial translation; (2) a bilingual community member edited the translation; (3) a certified medical translator edited the revision; (4) a focus group of N=5 bilingual community members made contextual edits; (5) a back-translation was performed; (6) an additional bilingual focus group examined the final version for compatibility; and (7) the medical translator certified the accuracy of the final version. T-tests examined differences between those who completed the measure in Spanish vs English. Results: Of the N=100 survey respondents, N=42 completed the SDSCL-25 in Spanish. Those who took the measure in Spanish showed no differences in frequency of reports of delayed sleep phase (p=0.28), snoring (p=0.85), morning dry mouth (p=0.87), choking/gasping (p=0.09), uncomfortable sensations in legs (p=0.25), urge to move legs (p=0.09), cataplexy (p=0.09), sleep paralysis (p=0.12), sleepwalking (p=0.08), or bruxism (p=0.13). Respondents in Spanish reported lower frequency of insufficient sleep (p=0.01), variability in bedtime (p=0.02), difficulty falling asleep (p=0.002), difficulty staying asleep (p=0.01), early morning awakenings (p=0.02), daytime tiredness/fatigue (p=0.006), phase advance (p=0.0003), daytime sleepiness (p=0.03), loud snoring (0.002), breathing pauses (p=0.049), frequent awakenings (p=0.0007), hypnogogic/pompic hallucinations (p=0.003), nightmares (p=0.047), panic awakenings (p=0.01), and overall sleep disturbance (p=0.043). Conclusion: The present study describes a Spanish translation of the SDSCL-25. For those that took the Spanish version, there were lower reported frequencies of insufficient sleep, variability in bedtime, insomnia symptoms, daytime sleepiness and tiredness/fatigue, phase advance, sleep apnea symptoms, frequent awakenings, hypnogogic/pompic hallucinations, nightmares, panic awakenings, and overall sleep disturbance. Support (If Any):